GE_GERICHTE C/18974/2015 vom 2. März 2016 - GE Cour de justice (2016)
AVIS DE SAISIE ; DÉBITEUR; DIRECTIVE(INJONCTION) ; DROIT À DES CONDITIONS MINIMALES D'EXISTENCE ; OBLIGATION D'ENTRETIEN ; CONJOINT | CC.177;